Efektivitas Pemanfaatan Green House Sebagai Sumber Belajar Biologi dalam Meningkatkan Motivasi Siswa Kelas X SMAN 12 Bone - Ajriana; Sri Wahyuni; Muliana (Journal of Mandalika Literature, 2025)
This study aims to determine how the effectiveness of Green House utilization as a biology learning resource in increasing the motivation of class X students of SMAN 12 Bone. The research used was quantitative research with the type of Pre-Experimental Design research with the type of One Group Pre-Test and Post-Test Design. The population consisted of 9 classes and sampling was done using purposive sampling technique. The research sample was class X.4 with 35 students. The data collection techniques used in this study were giving pre and post tests of student learning motivation questionnaires, and documentation. The results of descriptive analysis using a learning motivation questionnaire to find out how student learning motivation is obtained a value that is in the interval 69-84 where the value is categorized as high. Furthermore, the results of inferential analysis were carried out using the SPSS Version 23 application. The results of normality and homogeneity tests obtained normal and homogeneous data results. While the hypothesis test was carried out using Paired sample pre-test post-test, the significance value was smaller than 0.05, which was 0.000 where sig (2-tailed) ˂ 0.05. This proves that there is a significant effectiveness of Paired sample pre-test post-test. This proves that there is significant effectiveness between variable X and variable Y. The conclusion of the study shows that the use of Green House as a learning resource is effective in increasing student learning motivation.